INSON RESURSLARI VA IJRO INTIZOMINI TA’MINLASHDA AXBOROT-KOMMUNIKATSIYA VOSITALARINING AHAMIYATI - Ergashev Anvarjon Erkin o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article analyzes the role of information and communication technologies (ICT) in human resource management and ensuring execution discipline. It examines how digital tools contribute to recruitment, employee placement, performance evaluation, motivation, and working time control. The study highlights the importance of electronic document management systems, KPI-based assessment models, and monitoring tools in improving transparency, efficiency, and accountability. In addition, it discusses the impact of ICT on strengthening labor discipline and reducing human errors in management processes. The article also considers international experiences in the implementation of digital HRM systems. Based on the analysis, conclusions and recommendations are presented for improving organizational efficiency through wider adoption of ICT.